Central America, 1821-1871 : liberalism before liberal reform - Gudmundson, Lowell (University of Alabama Press, 1995)
Central America and its ill-fated federation (1824-1839) are often viewed as the archetype of the "anarchy" of early independent Spanish America. This book consists of two interralted essays dealing with the economic, social, and political changes that took place in Central America, changes that let to both Liberal regime consolidation and export agricultural development after the middle of the last century. The authors provide a challenging reinterpretation of Central American history and the most detailed analysis available in English of this most heterogeneous and obscure of soc.